Heating and warm-keeping nano aerogel fiber and preparation method thereof
By using heat-inhibiting and warm nano-aerogel fibers composed of composite aerogel, modified wool fiber and phase change material, the problems of uneven heating and poor flexibility of existing heating materials are solved, and more efficient heating and warming performance is achieved.
Patent Information
- Application Number
- CN202510406915.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-02
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-04-02
AI Technical Summary
Existing heating materials have problems such as uneven heating, poor flexibility and possible electromagnetic radiation, and common warm insulation materials are difficult to meet demand in extremely cold environments.
The heat-insulating nanoaerogel fiber consisting of composite aerogel, modified wool fiber and phase change material is used to prepare composite aerogel by composite of boron nitride nanosheets modified sodium silicate and acetylacetonate vanadyloxy, and nanoaerogel fibers are prepared by supercritical drying technology.
It improves the heating efficiency and warming performance of the fiber, enhances the structural stability and mechanical properties of the fiber, reduces the loss of heat, and provides a more uniform and long-lasting warming effect.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aerogel fibers, and in particular to a heat-generating and heat-retaining nano aerogel fiber and a preparation method thereof. Background Art
[0002] With the continuous improvement of people's demand for warmth and the rapid development of science and technology, traditional heating materials such as metal wire heating and carbon fiber heating, although they can generate heat, have problems such as uneven heating, poor flexibility and possible electromagnetic radiation. Among the common thermal insulation materials, cotton fibers have large pores and relatively high thermal conductivity, and their thermal insulation performance cannot meet the needs of extremely cold environments. Although down has good thermal insulation performance, it is easily affected by moisture, and the thermal insulation effect is greatly reduced after being damp. In addition, its resources are limited and the cost is high. The thermal insulation performance of synthetic fibers such as polyester fibers is mainly based on preventing heat loss. When facing extremely cold environments or long-term cold exposure, its thermal insulation effect gradually cannot meet the needs. In view of this, we propose a heat-generating and thermal insulation nano aerogel fiber and a preparation method thereof. Summary of the invention
[0003] The object of the present invention is to provide a heat-generating and heat-retaining nano-aerogel fiber and a preparation method thereof, so as to solve the problems raised in the above-mentioned background technology.
[0004] To achieve the above-mentioned purpose, the present invention provides a heat-generating and heat-retaining nano-aerogel fiber, comprising the following components: composite aerogel, modified wool fiber, and phase change material; Among them, the composite aerogel is prepared by modifying sodium silicate with boron nitride nanosheets and compounding it with vanadium acetylacetonate.
[0005] Preferably, the preparation method of the composite aerogel is as follows: S1.1. Weigh the following components in parts by weight respectively: 50-70 parts by weight of sodium silicate, 10-20 parts by weight of boron nitride nanosheets, and 5-15 parts by weight of vanadyl acetylacetonate; S1.2, dissolving sodium silicate in deionized water to obtain a sodium silicate solution with a mass percentage concentration of 10-30%; ultrasonically dispersing the boron nitride nanosheets in ethanol to form a uniform boron nitride nanosheet suspension; S1.3, adding the boron nitride nanosheet suspension to the sodium silicate solution, the dropping time is 0.5-1h, and vigorously stirring at a speed of 800-1000rpm, maintaining the temperature of the mixed solution at 20-40°C; continuing to stir the reaction at a speed of 500-600rpm for 2-4h, and adjusting the pH value of the mixed solution to 8-10 with a sodium hydroxide solution with a concentration of 0.1-1mol / L to obtain a modified sodium silicate solution; Borides have special infrared radiation properties. When aerogels are used for heating and warmth preservation, these borides can enhance the aerogels' absorption and emission of infrared radiation. When infrared rays are irradiated onto aerogels, borides can better absorb these infrared rays and convert them into heat energy for storage. At the same time, aerogels themselves also emit infrared rays to maintain temperature. Borides can improve the efficiency of this infrared emission, thereby enhancing the heating and warmth preservation effects. Borides in aerogels can reduce the effective thermal conductivity of aerogels by scattering and reflecting heat. Their presence changes the heat transfer path in aerogels, making it more difficult for heat to be conducted through aerogels, reducing heat loss and thereby improving heating and warmth preservation properties. In addition, borides can be adsorbed on the surface of phase change materials to form a protective film, enabling the phase change materials to better play the role of storing and releasing energy in the nanopores of aerogels, thereby improving the overall heating and warmth preservation effects.
[0006] Boron nitride particles will be intertwined and stacked in the aerogel to form a three-dimensional network structure. These particles are combined together through interactions such as van der Waals forces, hydrogen bonds or chemical bonds, forming a relatively uniform distribution in the aerogel. During the preparation process of the aerogel, there will inevitably be some gaps between the particles, and these gaps form the pores of the aerogel.
[0007] Borides have high hardness and good mechanical stability. When they are doped into sodium silicate aerogel, they can strengthen the skeleton structure of the aerogel, making it stronger and reducing structural damage caused by external forces during use, thereby improving the durability of the aerogel.
[0008] S1.4, dissolving vanadyl acetylacetonate in ethanol to obtain a vanadyl acetylacetonate solution with a concentration of 0.1-0.5 mol / L; adding the vanadyl acetylacetonate solution to the modified sodium silicate solution at a rate of 1-2 mL / min, while stirring at a speed of 300-600 rpm to obtain a mixed solution; Vanadyl acetylacetonate itself has a certain thermal stability and is not easy to decompose under high temperature conditions. Therefore, introducing it into the composite aerogel can help improve the thermal stability of the overall material. In addition, vanadyl acetylacetonate can enhance the structural stability of the aerogel through synergistic effects with other materials (such as sodium silicate and boron nitride nanosheets), so that it can still maintain good mechanical properties under multiple cycles of compression, torsion and other loads.
[0009] S1.5, adding a hydrochloric acid solution with a concentration of 1-2 mol / L dropwise to the mixed solution until the pH value of the mixed solution reaches 3-5 to form a gel; and then subjecting the formed gel to an aging treatment; S1.6. Place the aged gel into an autoclave and use carbon dioxide as a supercritical fluid for supercritical drying for 10-12 hours to obtain a composite aerogel.
[0010] Preferably, in S1.2, the ultrasonic power is 100-200 W, and the ultrasonic time is 30-60 min.
[0011] Preferably, in S1.5, the aging treatment is to heat the gel at a temperature of 40-60° C. and a relative humidity of 50-70% for 12-48 hours.
[0012] Preferably, in S1.6, supercritical drying is firstly to inject carbon dioxide into the autoclave to make it reach a supercritical state at a temperature of 30-40°C and a high pressure of 7-10MPa, and then release the carbon dioxide to remove the solvent in the gel to obtain the composite aerogel.
[0013] On the other hand, the present invention provides a method for preparing a heat-generating and heat-retaining nano-aerogel fiber, which is used to prepare any of the heat-generating and heat-retaining nano-aerogel fibers described above, comprising the following steps: S2.1. Weigh the following components in parts by weight respectively: 50-70 parts by weight of composite aerogel, 20-40 parts by weight of wool fiber, 10-20 parts by weight of phase change material, and 2-5 parts by weight of γ-aminopropyltriethoxysilane; S2.2, dissolving the composite aerogel in ethanol, stirring with a magnetic stirrer at a speed of 300-400 rpm at room temperature, and continuously stirring for 3-5 hours to obtain a composite aerogel solution with a mass percentage concentration of 15-25%; S2.3, put the phase change material into an oil bath, heat it to 60-70°C, melt it completely, and stir the melted phase change material to make it a uniform liquid phase change material; Phase change materials can undergo phase changes according to temperature changes, from solid to liquid or vice versa. During this process, phase change materials will absorb or release a large amount of latent heat, and the temperature remains almost unchanged; when the ambient temperature rises, the phase change material melts and absorbs heat, thereby delaying the rise in temperature around the fiber; when the ambient temperature drops, it solidifies and releases heat, slowing down the temperature drop, which enables the heat-generating and warm nano aerogel fibers to automatically adjust the temperature and provide a relatively stable and comfortable thermal environment.
[0014] S2.4, placing the wool fiber in a detergent solution with a mass percentage concentration of 1-2%, stirring and washing at 40-50°C for 30-60 minutes to remove impurities such as grease and dust on the surface of the wool fiber; then rinsing the wool fiber with deionized water until the pH value of the rinsing solution is 6-8, and then drying in an oven at a temperature of 60-70°C to constant weight to obtain pretreated wool fiber; S2.5, dissolving γ-aminopropyltriethoxysilane in ethanol to obtain a γ-aminopropyltriethoxysilane solution with a mass percentage concentration of 6-10%; soaking the pretreated wool fiber in the γ-aminopropyltriethoxysilane solution, and after the soaking is completed, drying the wool fiber in an oven at 70-80° C. for 1-2 hours to obtain a surface-modified wool fiber; γ-aminopropyltriethoxysilane can form a hydrophobic silicone film on the fiber surface, reducing the surface energy of the fiber and making it have better waterproof performance. In a humid environment, it is difficult for water to penetrate into the fiber, thereby reducing heat loss caused by water absorption and helping to maintain the thermal insulation performance of the fiber. The ethoxy group in γ-aminopropyltriethoxysilane can react with the inorganic components in the aerogel fiber, and the amino group can interact with the organic polymer chain, thereby enhancing the bonding force between the inorganic phase and the organic phase, and significantly improving the mechanical properties of the fiber, such as strength and toughness. In addition, the amino group also has certain antibacterial properties, which can inhibit the growth and reproduction of bacteria on the fiber surface, reducing the odor caused by bacterial growth and potential health threats.
[0015] S2.6, immersing the surface-modified wool fiber in the composite aerogel solution, and at the same time, dropping the pretreated liquid phase change material into the impregnation system at a rate of 1-5 mL / min, and stirring the impregnation system at a speed of 200-300 rpm, and the stirring and impregnation time is 8-12 h; S2.7. After the impregnation is completed, the system containing the wool fiber is taken out from the solution for gelation reaction; after the gelation reaction is completed, carbon dioxide is used as a supercritical fluid, and supercritical drying is carried out at a temperature of 35-40°C and a pressure of 8-9MPa. The drying time is 12-24h to obtain heat-generating and heat-retaining nano aerogel fibers.
[0016] Preferably, the phase change material is palmitic acid or myristic acid.
[0017] Preferably, in S2.3, the stirring speed after melting is 400-600 rpm, and the stirring time is 10-15 min.
[0018] Preferably, in S2.5, the soaking temperature is 35-45°C, and the soaking time is 3-5h.
[0019] Preferably, in S2.7, the gelation reaction is performed by placing the system containing the wool fibers in a constant temperature and humidity chamber, with the temperature set at 45-55°C, the relative humidity set at 55-65%, and the gelation time being 18-30 hours.
[0020] Compared with the prior art, the present invention has the following beneficial effects: 1. In this heat-generating and thermal-insulating nano-aerogel fiber and its preparation method, the addition of borides can absorb infrared radiation and convert it into thermal energy, thereby improving the heating efficiency of the fiber; at the same time, borides can also enhance the infrared emission ability of the fiber itself. When the fiber temperature rises, it can better dissipate the heat in the form of infrared radiation to maintain the surrounding warm environment; in addition, when heat is transferred in the fiber, the boride will cause the heat to scatter and reflect, increase the resistance to heat transfer, and thus reduce the effective thermal conductivity of the fiber, which enables the fiber to better prevent heat loss and improve thermal insulation performance.
[0021] 2. In this kind of heat-generating and thermal-insulating nano-aerogel fiber and its preparation method, vanadium acetylacetonate itself has a certain thermal stability and is not easy to decompose under high temperature conditions. Therefore, introducing it into the composite aerogel can help improve the thermal stability of the overall material; in addition, vanadium acetylacetonate can enhance the structural stability of the aerogel through synergistic effects with other materials (such as sodium silicate and boron nitride nanosheets), so that it can still maintain good mechanical properties under multiple cycles of compression, torsion and other loads. DETAILED DESCRIPTION
[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0023] The present invention provides a heat-generating and heat-retaining nano-aerogel fiber, comprising the following components: composite aerogel, modified wool fiber, and phase change material; Among them, the composite aerogel is prepared by modifying sodium silicate with boron nitride nanosheets and compounding it with vanadium acetylacetonate.
[0024] Unless otherwise specified, the parts of the present invention are all parts by mass, the percentages are all percentages by mass, and the range of ethanol concentration is 90-95%.
[0025] The phase change material is palmitic acid or myristic acid, preferably palmitic acid.
[0026] Embodiment 1: A heat-generating and heat-retaining nano-aerogel fiber and a preparation method thereof, comprising the following steps: S2.1. Weigh the following components in parts by weight respectively: 60 parts by weight of composite aerogel, 30 parts by weight of wool fiber, 15 parts by weight of palmitic acid, and 4 parts by weight of γ-aminopropyltriethoxysilane; S2.2, dissolving the composite aerogel in ethanol, stirring with a magnetic stirrer at 400 rpm at room temperature for 4 h to obtain a composite aerogel solution with a mass percentage concentration of 20%; S2.3, put palmitic acid into an oil bath, heat it to 65°C, and completely melt it. Stir the melted palmitic acid at a speed of 500 rpm for 15 min to make it into a uniform liquid palmitic acid; S2.4, place the wool fiber in a detergent solution with a mass percentage concentration of 2%, and stir and wash at 40°C for 45 minutes to remove impurities such as grease and dust on the surface of the wool fiber; then rinse the wool fiber with deionized water until the pH value of the rinse solution is 7, and then dry it in an oven at a temperature of 60°C to constant weight; S2.5, dissolving γ-aminopropyltriethoxysilane in ethanol to obtain a γ-aminopropyltriethoxysilane solution with a mass percentage concentration of 8%; soaking the pretreated wool fiber in the γ-aminopropyltriethoxysilane solution at a soaking temperature of 40° C. for 4 hours, and after the soaking is completed, drying the wool fiber in an oven at 70° C. for 1 hour to obtain a surface-modified wool fiber; S2.6, immersing the surface-modified wool fiber in the composite aerogel solution, and at the same time, adding the pretreated liquid palmitic acid to the impregnation system at a rate of 2 mL / min, and stirring the impregnation system at a speed of 300 rpm for 12 h; S2.7. After the impregnation is completed, the system containing the wool fiber is taken out from the solution and placed in a constant temperature and humidity chamber for gelation reaction at a temperature of 50°C, a relative humidity of 60%, and a gelation time of 25 hours. After the gelation reaction is completed, carbon dioxide is used as a supercritical fluid and supercritical drying is carried out at a temperature of 40°C and a pressure of 9MPa for 15 hours to obtain heat-generating and heat-retaining nano aerogel fibers.
[0027] The preparation method of the composite aerogel is as follows: S1.1. Weigh the following components in parts by weight respectively: 60 parts by weight of sodium silicate, 12 parts by weight of boron nitride nanosheets, and 10 parts by weight of vanadyl acetylacetonate; S1.2, dissolving sodium silicate in deionized water to obtain a sodium silicate solution with a mass percentage concentration of 20%; ultrasonically dispersing the boron nitride nanosheets in ethanol at an ultrasonic power of 200 W and an ultrasonic time of 40 min to form a uniform boron nitride nanosheet suspension; S1.3, adding the boron nitride nanosheet suspension to the sodium silicate solution for 0.5 h, stirring vigorously at 1000 rpm, and maintaining the temperature of the mixed solution at 30 ° C; continuing to stir the reaction at 600 rpm for 3 h, using a sodium hydroxide solution with a concentration of 0.5 mol / L to adjust the pH value of the mixed solution to 9, to obtain a doped modified sodium silicate solution; S1.4, dissolving vanadium acetylacetonate in ethanol to obtain a vanadium acetylacetonate solution with a concentration of 0.3 mol / L; adding the vanadium acetylacetonate solution to the doped modified sodium silicate solution at a rate of 2 mL / min, while stirring at a speed of 400 rpm to obtain a mixed solution; S1.5, adding a 1 mol / L hydrochloric acid solution dropwise to the mixed solution until the pH value of the mixed solution reaches 4 to form a gel; then heating the formed gel at a temperature of 60°C and a relative humidity of 70% for aging treatment, and the aging time is 15 hours; S1.6. Place the aged gel into an autoclave and use carbon dioxide as a supercritical fluid to perform supercritical drying at a temperature of 40°C and a pressure of 8 MPa for 10 hours to obtain a composite aerogel.
[0028] Embodiment 2: A heat-generating and heat-retaining nano-aerogel fiber and a preparation method thereof, comprising the following steps: S2.1. Weigh the following components in parts by weight respectively: 60 parts by weight of composite aerogel, 30 parts by weight of wool fiber, 15 parts by weight of palmitic acid, and 4 parts by weight of γ-aminopropyltriethoxysilane; S2.2, dissolving the composite aerogel in ethanol, stirring with a magnetic stirrer at 400 rpm at room temperature for 4 h to obtain a composite aerogel solution with a mass percentage concentration of 20%; S2.3, put palmitic acid into an oil bath, heat it to 65°C, and completely melt it. Stir the melted palmitic acid at a speed of 500 rpm for 15 min to make it into a uniform liquid palmitic acid; S2.4, place the wool fiber in a detergent solution with a mass percentage concentration of 2%, and stir and wash at 40°C for 45 minutes to remove impurities such as grease and dust on the surface of the wool fiber; then rinse the wool fiber with deionized water until the pH value of the rinse solution is 7, and then dry it in an oven at a temperature of 60°C to constant weight; S2.5, dissolving γ-aminopropyltriethoxysilane in ethanol to obtain a γ-aminopropyltriethoxysilane solution with a mass percentage concentration of 8%; soaking the pretreated wool fiber in the γ-aminopropyltriethoxysilane solution at a soaking temperature of 40° C. for 4 hours, and after the soaking is completed, drying the wool fiber in an oven at 70° C. for 1 hour to obtain a surface-modified wool fiber; S2.6, immersing the surface-modified wool fiber in the composite aerogel solution, and at the same time, adding the pretreated liquid palmitic acid to the impregnation system at a rate of 2 mL / min, and stirring the impregnation system at a speed of 300 rpm for 12 h; S2.7. After the impregnation is completed, the system containing the wool fiber is taken out from the solution and placed in a constant temperature and humidity chamber for gelation reaction at a temperature of 50°C, a relative humidity of 60%, and a gelation time of 25 hours. After the gelation reaction is completed, carbon dioxide is used as a supercritical fluid and supercritical drying is carried out at a temperature of 40°C and a pressure of 9MPa for 15 hours to obtain heat-generating and heat-retaining nano aerogel fibers.
[0029] The preparation method of the composite aerogel is as follows: S1.1. Weigh the following components in parts by weight respectively: 60 parts by weight of sodium silicate, 15 parts by weight of boron nitride nanosheets, and 10 parts by weight of vanadyl acetylacetonate; S1.2, dissolving sodium silicate in deionized water to obtain a sodium silicate solution with a mass percentage concentration of 20%; ultrasonically dispersing the boron nitride nanosheets in ethanol at an ultrasonic power of 200 W and an ultrasonic time of 40 min to form a uniform boron nitride nanosheet suspension; S1.3, adding the boron nitride nanosheet suspension to the sodium silicate solution for 0.5 h, stirring vigorously at 1000 rpm, and maintaining the temperature of the mixed solution at 30 ° C; continuing to stir the reaction at 600 rpm for 3 h, using a sodium hydroxide solution with a concentration of 0.5 mol / L to adjust the pH value of the mixed solution to 9, to obtain a doped modified sodium silicate solution; S1.4, dissolving vanadium acetylacetonate in ethanol to obtain a vanadium acetylacetonate solution with a concentration of 0.3 mol / L; adding the vanadium acetylacetonate solution to the doped modified sodium silicate solution at a rate of 2 mL / min, while stirring at a speed of 400 rpm to obtain a mixed solution; S1.5, adding a 1 mol / L hydrochloric acid solution dropwise to the mixed solution until the pH value of the mixed solution reaches 4 to form a gel; then heating the formed gel at a temperature of 60°C and a relative humidity of 70% for aging treatment, and the aging time is 15 hours; S1.6. Place the aged gel into an autoclave and use carbon dioxide as a supercritical fluid to perform supercritical drying at a temperature of 40°C and a pressure of 8 MPa for 10 hours to obtain a composite aerogel.
[0030] Embodiment 3: A heat-generating and heat-retaining nano-aerogel fiber and a preparation method thereof, comprising the following steps: S2.1. Weigh the following components in parts by weight respectively: 60 parts by weight of composite aerogel, 30 parts by weight of wool fiber, 15 parts by weight of palmitic acid, and 4 parts by weight of γ-aminopropyltriethoxysilane; S2.2, dissolving the composite aerogel in ethanol, stirring with a magnetic stirrer at 400 rpm at room temperature for 4 h to obtain a composite aerogel solution with a mass percentage concentration of 20%; S2.3, put palmitic acid into an oil bath, heat it to 65°C, and completely melt it. Stir the melted palmitic acid at a speed of 500 rpm for 15 min to make it into a uniform liquid palmitic acid; S2.4, place the wool fiber in a detergent solution with a mass percentage concentration of 2%, and stir and wash at 40°C for 45 minutes to remove impurities such as grease and dust on the surface of the wool fiber; then rinse the wool fiber with deionized water until the pH value of the rinse solution is 7, and then dry it in an oven at a temperature of 60°C to constant weight; S2.5, dissolving γ-aminopropyltriethoxysilane in ethanol to obtain a γ-aminopropyltriethoxysilane solution with a mass percentage concentration of 8%; soaking the pretreated wool fiber in the γ-aminopropyltriethoxysilane solution at a soaking temperature of 40° C. for 4 hours, and after the soaking is completed, drying the wool fiber in an oven at 70° C. for 1 hour to obtain a surface-modified wool fiber; S2.6, immersing the surface-modified wool fiber in the composite aerogel solution, and at the same time, adding the pretreated liquid palmitic acid to the impregnation system at a rate of 2 mL / min, and stirring the impregnation system at a speed of 300 rpm for 12 h; S2.7. After the impregnation is completed, the system containing the wool fiber is taken out from the solution and placed in a constant temperature and humidity chamber for gelation reaction at a temperature of 50°C, a relative humidity of 60%, and a gelation time of 25 hours. After the gelation reaction is completed, carbon dioxide is used as a supercritical fluid and supercritical drying is carried out at a temperature of 40°C and a pressure of 9MPa for 15 hours to obtain heat-generating and heat-retaining nano aerogel fibers.
[0031] The preparation method of the composite aerogel is as follows: S1.1. Weigh the following components in parts by weight respectively: 60 parts by weight of sodium silicate, 18 parts by weight of boron nitride nanosheets, and 10 parts by weight of vanadyl acetylacetonate; S1.2, dissolving sodium silicate in deionized water to obtain a sodium silicate solution with a mass percentage concentration of 20%; ultrasonically dispersing the boron nitride nanosheets in ethanol at an ultrasonic power of 200 W and an ultrasonic time of 40 min to form a uniform boron nitride nanosheet suspension; S1.3, adding the boron nitride nanosheet suspension to the sodium silicate solution for 0.5 h, stirring vigorously at 1000 rpm, and maintaining the temperature of the mixed solution at 30 ° C; continuing to stir the reaction at 600 rpm for 3 h, using a sodium hydroxide solution with a concentration of 0.5 mol / L to adjust the pH value of the mixed solution to 9, to obtain a doped modified sodium silicate solution; S1.4, dissolving vanadium acetylacetonate in ethanol to obtain a vanadium acetylacetonate solution with a concentration of 0.3 mol / L; adding the vanadium acetylacetonate solution to the doped modified sodium silicate solution at a rate of 2 mL / min, while stirring at a speed of 400 rpm to obtain a mixed solution; S1.5, adding a 1 mol / L hydrochloric acid solution dropwise to the mixed solution until the pH value of the mixed solution reaches 4 to form a gel; then heating the formed gel at a temperature of 60°C and a relative humidity of 70% for aging treatment, and the aging time is 15 hours; S1.6. Place the aged gel into an autoclave and use carbon dioxide as a supercritical fluid to perform supercritical drying at a temperature of 40°C and a pressure of 8 MPa for 10 hours to obtain a composite aerogel.
[0032] Embodiment 4: A heat-generating and heat-retaining nano-aerogel fiber and a preparation method thereof, comprising the following steps: S2.1. Weigh the following components in parts by weight respectively: 60 parts by weight of composite aerogel, 30 parts by weight of wool fiber, 15 parts by weight of palmitic acid, and 4 parts by weight of γ-aminopropyltriethoxysilane; S2.2, dissolving the composite aerogel in ethanol, stirring with a magnetic stirrer at 400 rpm at room temperature for 4 h to obtain a composite aerogel solution with a mass percentage concentration of 20%; S2.3, put palmitic acid into an oil bath, heat it to 65°C, and completely melt it. Stir the melted palmitic acid at a speed of 500 rpm for 15 min to make it into a uniform liquid palmitic acid; S2.4, place the wool fiber in a detergent solution with a mass percentage concentration of 2%, and stir and wash at 40°C for 45 minutes to remove impurities such as grease and dust on the surface of the wool fiber; then rinse the wool fiber with deionized water until the pH value of the rinse solution is 7, and then dry it in an oven at a temperature of 60°C to constant weight; S2.5, dissolving γ-aminopropyltriethoxysilane in ethanol to obtain a γ-aminopropyltriethoxysilane solution with a mass percentage concentration of 8%; soaking the pretreated wool fiber in the γ-aminopropyltriethoxysilane solution at a soaking temperature of 40° C. for 4 hours, and after the soaking is completed, drying the wool fiber in an oven at 70° C. for 1 hour to obtain a surface-modified wool fiber; S2.6, immersing the surface-modified wool fiber in the composite aerogel solution, and at the same time, adding the pretreated liquid palmitic acid to the impregnation system at a rate of 2 mL / min, and stirring the impregnation system at a speed of 300 rpm for 12 h; S2.7. After the impregnation is completed, the system containing the wool fiber is taken out from the solution and placed in a constant temperature and humidity chamber for gelation reaction at a temperature of 50°C, a relative humidity of 60%, and a gelation time of 25 hours. After the gelation reaction is completed, carbon dioxide is used as a supercritical fluid and supercritical drying is carried out at a temperature of 40°C and a pressure of 9MPa for 15 hours to obtain heat-generating and heat-retaining nano aerogel fibers.
[0033] The preparation method of the composite aerogel is as follows: S1.1. Weigh the following components in parts by weight respectively: 60 parts by weight of sodium silicate, 20 parts by weight of boron nitride nanosheets, and 10 parts by weight of vanadyl acetylacetonate; S1.2, dissolving sodium silicate in deionized water to obtain a sodium silicate solution with a mass percentage concentration of 20%; ultrasonically dispersing the boron nitride nanosheets in ethanol at an ultrasonic power of 200 W and an ultrasonic time of 40 min to form a uniform boron nitride nanosheet suspension; S1.3, adding the boron nitride nanosheet suspension to the sodium silicate solution for 0.5 h, stirring vigorously at 1000 rpm, and maintaining the temperature of the mixed solution at 30 ° C; continuing to stir the reaction at 600 rpm for 3 h, using a sodium hydroxide solution with a concentration of 0.5 mol / L to adjust the pH value of the mixed solution to 9, to obtain a doped modified sodium silicate solution; S1.4, dissolving vanadium acetylacetonate in ethanol to obtain a vanadium acetylacetonate solution with a concentration of 0.3 mol / L; adding the vanadium acetylacetonate solution to the doped modified sodium silicate solution at a rate of 2 mL / min, while stirring at a speed of 400 rpm to obtain a mixed solution; S1.5, adding a 1 mol / L hydrochloric acid solution dropwise to the mixed solution until the pH value of the mixed solution reaches 4 to form a gel; then heating the formed gel at a temperature of 60°C and a relative humidity of 70% for aging treatment, and the aging time is 15 hours; S1.6. Place the aged gel into an autoclave and use carbon dioxide as a supercritical fluid to perform supercritical drying at a temperature of 40°C and a pressure of 8 MPa for 10 hours to obtain a composite aerogel.
[0034] Embodiment 5: A heat-generating and heat-retaining nano-aerogel fiber and a preparation method thereof, comprising the following steps: S2.1. Weigh the following components in parts by weight respectively: 50 parts by weight of composite aerogel, 20 parts by weight of wool fiber, 10 parts by weight of palmitic acid, and 2 parts by weight of γ-aminopropyltriethoxysilane; S2.2, dissolving the composite aerogel in ethanol, stirring with a magnetic stirrer at a speed of 400 rpm at room temperature, and continuously stirring for 4 hours to obtain a composite aerogel solution with a mass percentage concentration of 15%; S2.3, put palmitic acid into an oil bath, heat it to 65°C, and completely melt it. Stir the melted palmitic acid at a speed of 500 rpm for 15 min to make it into a uniform liquid palmitic acid; S2.4, place the wool fiber in a detergent solution with a mass percentage concentration of 2%, and stir and wash at 40°C for 45 minutes to remove impurities such as grease and dust on the surface of the wool fiber; then rinse the wool fiber with deionized water until the pH value of the rinse solution is 7, and then dry it in an oven at a temperature of 60°C to constant weight; S2.5, dissolving γ-aminopropyltriethoxysilane in ethanol to obtain a γ-aminopropyltriethoxysilane solution with a mass percentage concentration of 6%; soaking the pretreated wool fiber in the γ-aminopropyltriethoxysilane solution at a soaking temperature of 40° C. for 4 hours, and after the soaking is completed, drying the wool fiber in an oven at 70° C. for 1 hour to obtain a surface-modified wool fiber; S2.6, immersing the surface-modified wool fiber in the composite aerogel solution, and at the same time, adding the pretreated liquid palmitic acid to the impregnation system at a rate of 2 mL / min, and stirring the impregnation system at a speed of 300 rpm for 12 h; S2.7. After the impregnation is completed, the system containing the wool fiber is taken out from the solution and placed in a constant temperature and humidity chamber for gelation reaction at a temperature of 50°C, a relative humidity of 60%, and a gelation time of 25 hours. After the gelation reaction is completed, carbon dioxide is used as a supercritical fluid and supercritical drying is carried out at a temperature of 40°C and a pressure of 9MPa for 15 hours to obtain heat-generating and heat-retaining nano aerogel fibers.
[0035] The preparation method of the composite aerogel is as follows: S1.1. Weigh the following components in parts by weight respectively: 60 parts by weight of sodium silicate, 18 parts by weight of boron nitride nanosheets, and 5 parts by weight of vanadyl acetylacetonate; S1.2, dissolving sodium silicate in deionized water to obtain a sodium silicate solution with a mass percentage concentration of 20%; ultrasonically dispersing the boron nitride nanosheets in ethanol at an ultrasonic power of 200 W and an ultrasonic time of 40 min to form a uniform boron nitride nanosheet suspension; S1.3, adding the boron nitride nanosheet suspension to the sodium silicate solution for 0.5 h, stirring vigorously at 1000 rpm, and maintaining the temperature of the mixed solution at 30 ° C; continuing to stir the reaction at 600 rpm for 3 h, using a sodium hydroxide solution with a concentration of 0.5 mol / L to adjust the pH value of the mixed solution to 9, to obtain a doped modified sodium silicate solution; S1.4, dissolving vanadium acetylacetonate in ethanol to obtain a vanadium acetylacetonate solution with a concentration of 0.3 mol / L; adding the vanadium acetylacetonate solution to the doped modified sodium silicate solution at a rate of 2 mL / min, while stirring at a speed of 400 rpm to obtain a mixed solution; S1.5, adding a 1 mol / L hydrochloric acid solution dropwise to the mixed solution until the pH value of the mixed solution reaches 4 to form a gel; then heating the formed gel at a temperature of 60°C and a relative humidity of 70% for aging treatment, and the aging time is 15 hours; S1.6. Place the aged gel into an autoclave and use carbon dioxide as a supercritical fluid to perform supercritical drying at a temperature of 40°C and a pressure of 8 MPa for 10 hours to obtain a composite aerogel.
[0036] Embodiment 6: A heat-generating and heat-retaining nano-aerogel fiber and a preparation method thereof, comprising the following steps: S2.1. Weigh the following components in parts by weight respectively: 65 parts by weight of composite aerogel, 30 parts by weight of wool fiber, 15 parts by weight of palmitic acid, and 4 parts by weight of γ-aminopropyltriethoxysilane; S2.2, dissolving the composite aerogel in ethanol, stirring with a magnetic stirrer at 400 rpm at room temperature for 4 h to obtain a composite aerogel solution with a mass percent concentration of 22%; S2.3, put palmitic acid into an oil bath, heat it to 65°C, and completely melt it. Stir the melted palmitic acid at a speed of 500 rpm for 15 min to make it into a uniform liquid palmitic acid; S2.4, place the wool fiber in a detergent solution with a mass percentage concentration of 2%, and stir and wash at 40°C for 45 minutes to remove impurities such as grease and dust on the surface of the wool fiber; then rinse the wool fiber with deionized water until the pH value of the rinse solution is 7, and then dry it in an oven at a temperature of 60°C to constant weight; S2.5, dissolving γ-aminopropyltriethoxysilane in ethanol to obtain a γ-aminopropyltriethoxysilane solution with a mass percentage concentration of 8%; soaking the pretreated wool fiber in the γ-aminopropyltriethoxysilane solution at a soaking temperature of 40° C. for 4 hours, and after the soaking is completed, drying the wool fiber in an oven at 70° C. for 1 hour to obtain a surface-modified wool fiber; S2.6, immersing the surface-modified wool fiber in the composite aerogel solution, and at the same time, adding the pretreated liquid palmitic acid to the impregnation system at a rate of 2 mL / min, and stirring the impregnation system at a speed of 300 rpm for 12 h; S2.7. After the impregnation is completed, the system containing the wool fiber is taken out from the solution and placed in a constant temperature and humidity chamber for gelation reaction at a temperature of 50°C, a relative humidity of 60%, and a gelation time of 25 hours. After the gelation reaction is completed, carbon dioxide is used as a supercritical fluid and supercritical drying is carried out at a temperature of 40°C and a pressure of 9MPa for 15 hours to obtain heat-generating and heat-retaining nano aerogel fibers.
[0037] The preparation method of the composite aerogel is as follows: S1.1. Weigh the following components in parts by weight respectively: 60 parts by weight of sodium silicate, 18 parts by weight of boron nitride nanosheets, and 10 parts by weight of vanadyl acetylacetonate; S1.2, dissolving sodium silicate in deionized water to obtain a sodium silicate solution with a mass percentage concentration of 20%; ultrasonically dispersing the boron nitride nanosheets in ethanol at an ultrasonic power of 200 W and an ultrasonic time of 40 min to form a uniform boron nitride nanosheet suspension; S1.3, adding the boron nitride nanosheet suspension to the sodium silicate solution for 0.5 h, stirring vigorously at 1000 rpm, and maintaining the temperature of the mixed solution at 30 ° C; continuing to stir the reaction at 600 rpm for 3 h, using a sodium hydroxide solution with a concentration of 0.5 mol / L to adjust the pH value of the mixed solution to 9, to obtain a doped modified sodium silicate solution; S1.4, dissolving vanadium acetylacetonate in ethanol to obtain a vanadium acetylacetonate solution with a concentration of 0.3 mol / L; adding the vanadium acetylacetonate solution to the doped modified sodium silicate solution at a rate of 2 mL / min, while stirring at a speed of 400 rpm to obtain a mixed solution; S1.5, adding a 1 mol / L hydrochloric acid solution dropwise to the mixed solution until the pH value of the mixed solution reaches 4 to form a gel; then heating the formed gel at a temperature of 60°C and a relative humidity of 70% for aging treatment, and the aging time is 15 hours; S1.6. Place the aged gel into an autoclave and use carbon dioxide as a supercritical fluid to perform supercritical drying at a temperature of 40°C and a pressure of 8 MPa for 10 hours to obtain a composite aerogel.
[0038] Embodiment 7: A heat-generating and heat-retaining nano-aerogel fiber and a preparation method thereof, comprising the following steps: S2.1. Weigh the following components in parts by weight respectively: 60 parts by weight of composite aerogel, 20 parts by weight of wool fiber, 10 parts by weight of palmitic acid, and 2 parts by weight of γ-aminopropyltriethoxysilane; S2.2, dissolving the composite aerogel in ethanol, stirring with a magnetic stirrer at 400 rpm at room temperature for 4 h to obtain a composite aerogel solution with a mass percentage concentration of 20%; S2.3, put palmitic acid into an oil bath, heat it to 65°C, and completely melt it. Stir the melted palmitic acid at a speed of 500 rpm for 15 min to make it into a uniform liquid palmitic acid; S2.4, place the wool fiber in a detergent solution with a mass percentage concentration of 2%, and stir and wash at 40°C for 45 minutes to remove impurities such as grease and dust on the surface of the wool fiber; then rinse the wool fiber with deionized water until the pH value of the rinse solution is 7, and then dry it in an oven at a temperature of 60°C to constant weight; S2.5, dissolving γ-aminopropyltriethoxysilane in ethanol to obtain a γ-aminopropyltriethoxysilane solution with a mass percentage concentration of 6%; soaking the pretreated wool fiber in the γ-aminopropyltriethoxysilane solution at a soaking temperature of 40° C. for 4 hours, and after the soaking is completed, drying the wool fiber in an oven at 70° C. for 1 hour to obtain a surface-modified wool fiber; S2.6, immersing the surface-modified wool fiber in the composite aerogel solution, and at the same time, adding the pretreated liquid palmitic acid to the impregnation system at a rate of 2 mL / min, and stirring the impregnation system at a speed of 300 rpm for 12 h; S2.7. After the impregnation is completed, the system containing the wool fiber is taken out from the solution and placed in a constant temperature and humidity chamber for gelation reaction at a temperature of 50°C, a relative humidity of 60%, and a gelation time of 25 hours. After the gelation reaction is completed, carbon dioxide is used as a supercritical fluid and supercritical drying is carried out at a temperature of 40°C and a pressure of 9MPa for 15 hours to obtain heat-generating and heat-retaining nano aerogel fibers.
[0039] The preparation method of the composite aerogel is as follows: S1.1. Weigh the following components in parts by weight respectively: 60 parts by weight of sodium silicate, 18 parts by weight of boron nitride nanosheets, and 5 parts by weight of vanadyl acetylacetonate; S1.2, dissolving sodium silicate in deionized water to obtain a sodium silicate solution with a mass percentage concentration of 20%; ultrasonically dispersing the boron nitride nanosheets in ethanol at an ultrasonic power of 200 W and an ultrasonic time of 40 min to form a uniform boron nitride nanosheet suspension; S1.3, adding the boron nitride nanosheet suspension to the sodium silicate solution for 0.5 h, stirring vigorously at 1000 rpm, and maintaining the temperature of the mixed solution at 30 ° C; continuing to stir the reaction at 600 rpm for 3 h, using a sodium hydroxide solution with a concentration of 0.5 mol / L to adjust the pH value of the mixed solution to 9, to obtain a doped modified sodium silicate solution; S1.4, dissolving vanadium acetylacetonate in ethanol to obtain a vanadium acetylacetonate solution with a concentration of 0.3 mol / L; adding the vanadium acetylacetonate solution to the doped modified sodium silicate solution at a rate of 2 mL / min, while stirring at a speed of 400 rpm to obtain a mixed solution; S1.5, adding a 1 mol / L hydrochloric acid solution dropwise to the mixed solution until the pH value of the mixed solution reaches 4 to form a gel; then heating the formed gel at a temperature of 60°C and a relative humidity of 70% for aging treatment, and the aging time is 15 hours; S1.6. Place the aged gel into an autoclave and use carbon dioxide as a supercritical fluid to perform supercritical drying at a temperature of 40°C and a pressure of 8 MPa for 10 hours to obtain a composite aerogel.
[0040] Comparative Example 1 The method of Example 6 was adopted, using uncompounded aerogel.
[0041] Comparative Example 2 The method of Example 6 was adopted without adding vanadyl acetylacetonate.
[0042] Comparative Example 3 The method of Example 6 was used to remove γ-aminopropyltriethoxysilane.
[0043] Comparative Example 4 The method of Example 6 is used to remove the phase change material.
[0044] The present invention discloses a heat-generating and heat-retaining nano-aerogel fiber prepared by composite aerogel and a preparation method thereof, wherein the performance index inspection items and inspection standards of the heat-generating and heat-retaining nano-aerogel fiber are as follows: Referring to the standard GB / T 10294-2008, the thermal conductivity of the fiber is measured to evaluate its thermal insulation performance. The lower the thermal conductivity, the better the thermal insulation performance of the fiber.
[0045] Accurately weigh a certain mass of fiber sample and place it in the sample cell of the differential scanning calorimeter. At the same time, place an equal amount of thermally inert material as a reference in the reference cell. Set the appropriate temperature scanning range and heating rate, start the instrument for testing, and record the curve of the heat flow signal changing with temperature to obtain the thermal performance parameters of the material such as phase change temperature and phase change enthalpy, and then calculate the heat storage efficiency. Generally, a higher heat storage efficiency means that the fiber can better store and release heat, providing a more lasting warmth effect.
[0046] According to the above standards, the heat-generating and heat-retaining nano-aerogel fibers prepared in the above Examples 1-7 and Comparative Examples 1-4 were tested, and the obtained data are shown in Table 1: Table 1 Performance data of heat-generating and heat-retaining nano aerogel fibers of Examples 1-7 and Comparative Examples 1-4 Table 1 It can be seen from Examples 1-4 that: when the mass ratio of boride to sodium silicate in the composite aerogel gradually increases, the thermal conductivity of the nano aerogel fiber gradually decreases, and the heat storage efficiency gradually increases, but when the mass ratio of boride to sodium silicate reaches a certain value, the thermal conductivity of the nano aerogel fiber increases significantly, and the heat storage efficiency decreases significantly. It can be seen that with the increase of the mass ratio of boride, the thermal conductivity and heat storage efficiency of the nano aerogel fiber are improved, but excessive increase may increase the thermal conductivity of the nano aerogel fiber and reduce the heat storage efficiency; Specifically, as the proportion of borides increases, aerogel fibers may be promoted to form a more uniform, fine and continuous nanoporous network structure, which can effectively extend the heat transfer path and make the heat conduction inside the fiber more difficult, thereby reducing the thermal conductivity. An appropriate increase in the boride content usually leads to an increase in the specific surface area of the nano aerogel fiber. A larger specific surface area means that the fiber has more contact area with the external environment and can better absorb and store heat. During the heat storage process, heat can be more fully distributed on the surface and internal pores of the fiber, thereby improving the heat storage efficiency.
[0047] A chemical reaction will occur between boride and sodium silicate to form a chemical bond. This chemical bonding can enhance the structural stability of the material and reduce heat loss caused by molecular vibration and thermal motion. At the same time, the existence of chemical bonds will also require heat to overcome a higher energy barrier during the transfer process, further reducing the thermal conductivity. In addition, the stable structure helps to maintain the storage state of heat inside the material, improving the heat storage efficiency, enabling it to store heat more effectively and release it slowly when needed.
[0048] Furthermore, by comparing Example 5, Example 6 and Example 7, it can be seen that when other components remain unchanged, only when the proportion of composite aerogel gradually increases, the thermal conductivity of the nano aerogel fiber is significantly reduced, and the heat storage efficiency is significantly increased. It can be seen that a special interface structure will be formed between different components in the composite aerogel, and these interfaces can act as a heat insulation barrier layer. When heat is transferred to the interface, due to the difference in thermal conductivity of different materials and the scattering effect of the interface, the heat transfer will be significantly hindered, which is similar to setting a barrier on the heat conduction path, further reducing the heat transfer efficiency and reducing the thermal conductivity; some components in the composite aerogel may undergo phase change when the temperature changes, absorbing or releasing a large amount of latent heat, thereby improving the heat storage capacity of the material; and other components can serve as a supporting skeleton or heat conduction channel to ensure the effective transfer and uniform distribution of heat inside the material, so that the heat storage efficiency is significantly improved.
[0049] Comparing Example 6 with Comparative Example 1, it can be seen that when uncompounded aerogel is used, the thermal conductivity of the nano aerogel fiber is significantly increased and the heat storage efficiency is significantly reduced.
[0050] Taking Example 6 as the optimal example and combining it with Comparative Example 2, it can be seen that in the composite aerogel preparation method, when vanadyl acetylacetonate is not added, the thermal conductivity of the nano aerogel fiber is significantly increased and the heat storage efficiency is significantly reduced; Without the addition of vanadium acetylacetonate, the thermal stability of the aerogel decreases, resulting in a weakening of its heat storage capacity at high temperatures; in addition, the thermal insulation performance of the aerogel depends on the stability of its nanoscale pore structure. If the pore structure is destroyed or unstable, its thermal insulation performance will be significantly reduced.
[0051] Example 6 is the best example, and combined with Comparative Example 3, it can be seen that when γ-aminopropyltriethoxysilane is removed, the thermal conductivity of the nano aerogel fiber is significantly increased, and the heat storage efficiency is significantly reduced; During the preparation process of nano aerogel fibers, γ-aminopropyltriethoxysilane can be hydrolyzed to form trace particles, providing crystallization centers for the precipitation of silicate. If a large number of crystallization centers are formed, these crystallization centers will compete with each other for growth space during the aerogel preparation process, resulting in relatively small and more evenly distributed aerogel pores, which reduces the thermal conductivity. If it is removed, the pores of the aerogel fibers will become larger, resulting in a smoother heat conduction path in the aerogel fibers, thereby significantly increasing the thermal conductivity, further affecting the crystallization process, making it impossible to form an effective heat storage structure, reducing the material's ability to store heat, and significantly reducing the heat storage efficiency.
[0052] Example 6 is the best example, and combined with Comparative Example 4, it can be seen that when the phase change material is removed, the thermal conductivity of the nano aerogel fiber increases significantly, and the heat storage efficiency decreases significantly; Phase change materials can play a role in increasing thermal resistance in nano aerogel fibers. When phase change materials are present, the heat transfer process needs to overcome the energy barrier when the phase change material undergoes phase change, thereby hindering the rapid transfer of heat and reducing the thermal conductivity. When the phase change material is removed, this thermal resistance disappears, and heat is more easily conducted through the aerogel fiber, resulting in a significant increase in thermal conductivity. Phase change materials can undergo phase changes within a specific temperature range and absorb or release a large amount of latent heat to store and release energy, thereby improving heat storage efficiency. When the phase change material is removed, the nano aerogel fiber loses this efficient phase change latent heat storage mechanism and can only rely on its own sensible heat to store heat. However, the sensible heat storage capacity is relatively weak, resulting in a significant reduction in heat storage efficiency.
[0053] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments. The above embodiments and descriptions are only preferred examples of the present invention and are not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A heat-generating and heat-retaining nano-aerogel fiber, characterized in that: It includes the following components: composite aerogel, modified wool fiber, phase change material; Among them, the composite aerogel is prepared by modifying sodium silicate with boron nitride nanosheets and compounding it with vanadium acetylacetonate.
2. The heat-generating and heat-retaining nano aerogel fiber according to claim 1, characterized in that: The preparation method of the composite aerogel is as follows: S1.
1. Weigh the following components in parts by weight respectively: 50-70 parts by weight of sodium silicate, 10-20 parts by weight of boron nitride nanosheets, and 5-15 parts by weight of vanadyl acetylacetonate; S1.2, dissolving sodium silicate in deionized water to obtain a sodium silicate solution with a mass percentage concentration of 10-30%; ultrasonically dispersing the boron nitride nanosheets in ethanol to form a uniform boron nitride nanosheet suspension; S1.3, adding the boron nitride nanosheet suspension to the sodium silicate solution, the dropping time is 0.5-1h, stirring at a speed of 800-1000rpm, and maintaining the temperature of the mixed solution at 20-40°C; continuing to stir the reaction at a speed of 500-600rpm for 2-4h, using a sodium hydroxide solution with a concentration of 0.1-1mol / L to adjust the pH value of the mixed solution to 8-10, to obtain a modified sodium silicate solution; S1.4, dissolving vanadyl acetylacetonate in ethanol to obtain a vanadyl acetylacetonate solution with a concentration of 0.1-0.5 mol / L; The vanadyl acetylacetonate solution is added to the modified sodium silicate solution at a rate of 1-2 mL / min, while stirring at a rate of 300-600 rpm to obtain a mixed solution; S1.5, adding a hydrochloric acid solution with a concentration of 1-2 mol / L dropwise to the mixed solution until the pH value of the mixed solution reaches 3-5 to form a gel; and then subjecting the formed gel to an aging treatment; S1.
6. Place the aged gel into an autoclave and use carbon dioxide as a supercritical fluid for supercritical drying for 10-12 hours to obtain a composite aerogel.
3. The heat-generating and heat-retaining nano aerogel fiber according to claim 2, characterized in that: In S1.2, the ultrasonic power is 100-200 W, and the ultrasonic time is 30-60 min.
4. The heat-generating and heat-retaining nano aerogel fiber according to claim 2, characterized in that: In S1.5, the aging treatment is to heat the gel at a temperature of 40-60° C. and a relative humidity of 50-70% for 12-48 hours.
5. The heat-generating and heat-retaining nano aerogel fiber according to claim 2, characterized in that: In S1.6, supercritical drying is to first inject carbon dioxide into the autoclave to make it reach a supercritical state at a temperature of 30-40°C and a high pressure of 7-10MPa, and then release the carbon dioxide to remove the solvent in the gel to obtain the composite aerogel.
6. A method for preparing a heat-generating and heat-retaining nano-aerogel fiber, used for preparing the heat-generating and heat-retaining nano-aerogel fiber as claimed in any one of claims 1 to 5, characterized in that: The preparation method of the heat-generating and heat-retaining nano aerogel fiber is as follows: S2.
1. Weigh the following components in parts by weight respectively: 50-70 parts by weight of composite aerogel, 20-40 parts by weight of wool fiber, 10-20 parts by weight of phase change material, and 2-5 parts by weight of γ-aminopropyltriethoxysilane; S2.2, dissolving the composite aerogel in ethanol, stirring with a magnetic stirrer at a speed of 300-400 rpm at room temperature, and continuously stirring for 3-5 hours to obtain a composite aerogel solution with a mass percentage concentration of 15-25%; S2.3, put the phase change material into an oil bath, heat it to 60-70°C, melt it completely, and stir the melted phase change material to make it a uniform liquid phase change material; S2.4, placing the wool fiber in a detergent solution with a mass percentage concentration of 1-2%, stirring and washing at 40-50°C for 30-60 minutes to remove grease and dust on the surface of the wool fiber; then rinsing the wool fiber with deionized water until the pH value of the rinse solution is 6-8, and then drying in an oven at a temperature of 60-70°C to constant weight to obtain pretreated wool fiber; S2.5, dissolving γ-aminopropyltriethoxysilane in ethanol to obtain a γ-aminopropyltriethoxysilane solution with a mass percentage concentration of 6-10%; soaking the pretreated wool fiber in the γ-aminopropyltriethoxysilane solution, and after the soaking is completed, drying the wool fiber in an oven at 70-80° C. for 1-2 hours to obtain a surface-modified wool fiber; S2.6, immersing the surface-modified wool fiber in the composite aerogel solution, and at the same time, dropping the pretreated liquid phase change material into the impregnation system at a rate of 1-5 mL / min, and stirring the impregnation system at a speed of 200-300 rpm, and the stirring and impregnation time is 8-12 h; S2.
7. After the impregnation is completed, the system containing the wool fiber is taken out from the solution for gelation reaction; after the gelation reaction is completed, carbon dioxide is used as a supercritical fluid, and supercritical drying is carried out at a temperature of 35-40°C and a pressure of 8-9MPa. The drying time is 12-24h to obtain heat-generating and heat-retaining nano aerogel fibers.
7. The method for preparing the heat-generating and heat-retaining nano-aerogel fiber according to claim 6, characterized in that: The phase change material is any one of palmitic acid or myristic acid.
8. The method for preparing the heat-generating and heat-retaining nano-aerogel fiber according to claim 6, characterized in that: In S2.3, the stirring speed after melting is 400-600 rpm, and the stirring time is 10-15 min.
9. The method for preparing the heat-generating and heat-retaining nano-aerogel fiber according to claim 6, characterized in that: In the S2.5, the soaking temperature is 35-45° C. and the soaking time is 3-5 hours.
10. The method for preparing the heat-generating and heat-retaining nano-aerogel fiber according to claim 6, characterized in that: In S2.7, the gelation reaction is to place the system containing the wool fibers in a constant temperature and humidity chamber, with the temperature set at 45-55°C, the relative humidity set at 55-65%, and the gelation time being 18-30 hours.
Citation Information
Patent Citations
High-performance thermal insulation material and preparation method thereof
CN101948296A
Boron nitride / graphene double-heat-conduction-base aerogel composite phase change material and preparation method thereof
CN111662688A
Flexible hydrophobic anisotropic cellulose nanofiber aerogel phase-change composite material and preparation method thereof
CN114032071A
Silica aerogel composite felt material, preparation method and application thereof
CN117902876A